Influence of behavioral and genetic variables on the prevalence of type 2 diabetes mellitus in middle-aged monks of Thailand - Hakaew, Utane; Sakphisutthikul, Chutikan; Laohasiriwong, Wongsa; Thammawongsa, Pittaya; Mahato, Roshan Kumar (Intelektual Pustaka Media Utama, 2024)
Diabetes mellitus (DM) and its associated complications present a major health problem for the Thai people, including Buddhist monks. This study aimed to identify the influence of behavioural and genetic variables on the prevalence of type 2 diabetes mellitus in middle-aged monks of Thailand. The study analyzed data from the health data centre of the Department of Public Health, Thailand, focusing on middle-aged monks in 76 provinces across 12 regions. The study recruited 6,408 Thai monks who met inclusion and exclusion criteria between October 2015-November 2019. Multivariable analysis was performed using a generalized linear mixed model, with adjusted odds ratios and 95% confidence intervals reported at a significance level of 0.05. Our study found that among the middle-aged monks of Thailand, 7.12% (95% CI: 6.49-7.78) had diabetes mellitus out of a total of 6,408. The results of our multivariable analysis showed that the following factors were associated with diabetes mellitus in monks of Thailand: respondents’ body mass index (BMI) ≥30 kg/m2 (AOR=4.26, 95% CI: 3.08-5.90, p-value <0.001), respondents with a family history of DM (AOR=3.37, 95% CI: 2.52-4.81, p-value<0.001), and respondent’s age ranges of 55-59 (AOR=2.87, 95% CI: 2.26-3.84, p-value<0.001), respectively. Diabetes millatus is significantly associated with the respondents who were obese, aged, and had a family history of DM. Therefore, a regular DM screening program as well as a timely health monitoring system for monks will enhance the diabetes control program in reducing the DM burden in Thailand.